Pristine, Chromogenic Polyaniline - A Novel Sorbent for Ion Exchange of Sodium Salts in Aqueous Solution - Deepa, N.A.; Dhivya, C.; Anbu Anjugam Vandarkuzhali, S.; Santhi, R.; Radha, N. (Asian Journal of Chemistry, 2014)
The sorption characteristics and ion exchange behaviour of polyaniline picrate (PANIPI) with various sodium salts (NaF, NaCl, NaBr, NaNO2, NaNO3, NaClO4, Na2SO4, NaH2PO4, NaOH, Na2CO3 and NaHCO3) have been studied. Langmuir, Freundlich, Temkin and Redlich-Peterson isotherm models are tested to describe the equilibrium established between PANIPI resin and solutions of sodium salt. The correlation coefficients show that Langmuir, Freundlich and Temkin models fit well for this sorption process. The sorption constants and negative DG° values indicate that the sorption of sodium salts on PANIPI is a favourable process. The ion exchange capacity (IEC) of the pristine PANIPI with these salts lie in the range of 1.96-3.49 meq/g and the separation factor (a) vary between 0.71-3.88 for the sodium salts used in the present study. These parameters indicate the suitability of PANIPI as a good ion exchanger. The UV-visible and FT-IR spectral changes before and after sorption are analysed to explain the sorption mechanism. The sorption capacities determined from the batch experiments are in the range 80-100 % for the sodium salts. The regenerative ability of PANIPI resin is ascertained from the column experiments conducted in three cycles. PANIPI is also found to possess antibacterial and antifungal activities. Hence, this novel chromogenic PANIPI resin has potential applications in desalination and ion detection processes.